2019
DOI: 10.1021/acsnano.8b07622
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Electric and Optical Tuning of KTaO3-Based Two-Dimensional Electron Gases with 5d Orbitals

Abstract: Controlling electronic processes in low-dimension electron systems is centrally important for both fundamental and applied researches. While most of the previous works focused on SrTiO 3 -based two-dimensional electron gases (2DEGs), here we report on a comprehensive investigation in this regard for amorphous-LaAlO 3 / KTaO 3 2DEGs with the Fermi energy ranging from ∼13 meV to ∼488 meV. The most important observation is the dramatic variation of the Rashba spin−orbit coupling (SOC) as Fermi energy sweeps throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
93
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 39 publications
17
93
1
1
Order By: Relevance
“…This advantage shows promising application for the optical nonvolatile devices. Zhang et al have expanded the application of optical gating to other oxide heterointerfaces such as KTaO 3 ‐based 2DEGs . In their KTaO 3 ‐based samples, the Fermi energy was tuned from 13 to 488 meV via optical gating leading to a control of the electronic structure and the Lifshitz transition, which echoes previous theoretical predictions and experimental findings in STO‐based 2DEGs …”
Section: Light/matter Interactionsupporting
confidence: 53%
See 1 more Smart Citation
“…This advantage shows promising application for the optical nonvolatile devices. Zhang et al have expanded the application of optical gating to other oxide heterointerfaces such as KTaO 3 ‐based 2DEGs . In their KTaO 3 ‐based samples, the Fermi energy was tuned from 13 to 488 meV via optical gating leading to a control of the electronic structure and the Lifshitz transition, which echoes previous theoretical predictions and experimental findings in STO‐based 2DEGs …”
Section: Light/matter Interactionsupporting
confidence: 53%
“…Light illumination can generate electron–hole pairs, which not only can contribute to the conductivity but also affect the diffusion of oxygen vacancies and thereby significantly modify the transport properties . For example, tunable persistent photoconductivity (PPC) has been reported in STO‐based heterointerfaces and combining light illumination with a gate bias, an enhancement of the resistance gatability has been demonstrated . In this section, we review the optical tunability and the underlying physical mechanisms.…”
Section: Light/matter Interactionmentioning
confidence: 99%
“…In the case of KTaO 3 , surface 2DEGs have been reported in ultrahigh vacuum conditions from oxygen vacancies [33,34]. Since these reports, a variety of means have been developed to produce interfacial 2DEGs in KTaO 3 , primarily through the introduction of polar/non-polar interfaces [35,36,37]. These interfaces have exhibited such interesting properties as optically tunable Rashba effect and greater Hall mobility than analogous LaAlO 3 /SrTiO 3 interfaces.…”
Section: Overview Of Complex Oxide Thin Films and Interfacesmentioning
confidence: 99%
“…24 For another 2DEG at an amorphous-LAO/ KTO interface, an experimental analysis of the weak antilocalization effect resulted in a Rashba coupling constant 0.1 eVÅ and a 50-fold enhanced Hall mobility of charge carriers. 26 Surprisingly, hysteretic magnetoresistance up to 25 K and anomalous Hall effect up to 70 K were observed at an EuO/ KTO interface. 27 It was shown that LaVO 3 /KTO heterostructure with strong spin-orbits interactions can be used to produce planar Hall effect, anisotropic magnetoresistance, and 2DEG.…”
Section: Introductionmentioning
confidence: 97%